2015
DOI: 10.1038/npp.2014.339
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in [11C]SB207145 PET Binding Associated with Change in Threat-Related Amygdala Reactivity in Humans

Abstract: Serotonin critically affects the neural processing of emotionally salient stimuli, including indices of threat; however, how alterations in serotonin signaling contribute to changes in brain function is not well understood. Recently, we showed in a placebo-controlled study of 32 healthy males that brain serotonin 4 receptor (5-HT4) binding, assessed with [(11)C]SB207145 PET, was sensitive to a 3-week intervention with the selective serotonin reuptake inhibitor fluoxetine, supporting it as an in vivo model for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 47 publications
(58 reference statements)
0
26
0
Order By: Relevance
“…All participants were recruited from the Copenhagen region via online advertisements for research projects approved by the Ethics Committee of Copenhagen and Frederiksberg, Denmark (H-1-2010-091, amendments: 28633, 30043;H-1-2010-085, amendments 28641, 33540;(KF)01-2006-20, amendment: 23504, 23830). Emotional faces fMRI data from 30 [Fisher et al, 2014b] and 32 [Fisher et al, 2015] of the participants included in the current study have been described in unrelated studies. Notably, some projects recruited only males and others recruited based on 5-HTTLPR genotype status (i.e., oversampling of L A L A and S 0 S 0 individuals).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants were recruited from the Copenhagen region via online advertisements for research projects approved by the Ethics Committee of Copenhagen and Frederiksberg, Denmark (H-1-2010-091, amendments: 28633, 30043;H-1-2010-085, amendments 28641, 33540;(KF)01-2006-20, amendment: 23504, 23830). Emotional faces fMRI data from 30 [Fisher et al, 2014b] and 32 [Fisher et al, 2015] of the participants included in the current study have been described in unrelated studies. Notably, some projects recruited only males and others recruited based on 5-HTTLPR genotype status (i.e., oversampling of L A L A and S 0 S 0 individuals).…”
Section: Participantsmentioning
confidence: 99%
“…Notably, all significant genotype and emotion condition effects remained when excluding these two participants. Emotional faces fMRI data from 30 [Fisher et al, 2014b] and 32 [Fisher et al, 2015] of the participants included in the current study have been described in unrelated studies.…”
Section: Participantsmentioning
confidence: 99%
“…From animal studies there is evidence that 5-HT 4 R binding potential (BP ND ) is inversely related to 5-HT tonus [ 34 , 35 ], which has been supported by subsequent genetic [ 36 ] and pharmacological intervention [ 37 ] studies in humans. Furthermore, we have previously shown that in healthy participants, 5-HT 4 R BP ND is associated with episodic memory [ 38 , 39 ], familial risk for depression [ 40 ], threat-related reactivity of amygdala [ 41 ], which is a key brain structure underlying personality trait N [ 42 ], as well as trait aggression in healthy males [ 43 ]. Together these findings suggest that the 5-HT 4 R may be linked to stable personality characteristics which warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have demonstrated changes in affective processing in response to pharmacological manipulation of 5-HT signaling (Fisher, Haahr, et al, 2015;Harmer, Bhagwagar, Cowen, & Goodwin, 2002;Harmer, Shelley, Cowen, & Goodwin, 2004;Mendelsohn et al, 2009;Molodtsova, 2008). Therefore, the noted differences in recall of negative words compared to positive and neutral words should also be investigated targeting the 5-HT 4 R with 5-HT acting interventions.…”
Section: Discussionmentioning
confidence: 99%